2017
DOI: 10.3390/su9122220
|View full text |Cite
|
Sign up to set email alerts
|

Value-Added-Based Accounting of CO2 Emissions: A Multi-Regional Input-Output Approach

Abstract: Abstract:In the era of globalization and international trade, the production-based CO 2 emissions accounting system, proposed by United Nations Framework Convention on Climate Change, can easily lead to a "carbon leakage" issue. Thus, the accounting of consumption-based carbon emissions and carbon emissions embodied in international trade has received considerable research attention. Nevertheless, researchers also indicated that the consumption-based principle has some weaknesses, for example, it leads the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 53 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…Higher income translates to higher consumption capacity and greater demands for environmental resource inputs. The Ghosh supply-push input-output model can capture the linkages of value-added with primary inputs, which has been used to estimate the enabled emissions of CO and air pollutants driven by the value added using the income-based accounting method (e.g., Liu et al, 2010;Zhang, 2010;Marques et al, 2013;Liang et al, 2016a,b;Liu and Fan, 2017). Furthermore, the method of structural decomposition analysis (SDA) enables researchers to examine the driving forces of resources, emissions and other physical quantities (e.g., Hoekstra and Van Den Bergh, 2002;Ang, 2012, 2017;Arto and Dietzenbacher, 2014;Malik et al, 2016;Deng and Xu, 2017;Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Higher income translates to higher consumption capacity and greater demands for environmental resource inputs. The Ghosh supply-push input-output model can capture the linkages of value-added with primary inputs, which has been used to estimate the enabled emissions of CO and air pollutants driven by the value added using the income-based accounting method (e.g., Liu et al, 2010;Zhang, 2010;Marques et al, 2013;Liang et al, 2016a,b;Liu and Fan, 2017). Furthermore, the method of structural decomposition analysis (SDA) enables researchers to examine the driving forces of resources, emissions and other physical quantities (e.g., Hoekstra and Van Den Bergh, 2002;Ang, 2012, 2017;Arto and Dietzenbacher, 2014;Malik et al, 2016;Deng and Xu, 2017;Wang et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…According to the benefit principle [19], the benefit-based proportional method (BPM) determines the cost allocation ratio of each pipeline company according to the economic benefit that the pipeline produces when laid into a utility tunnel. The economic benefit of each pipeline company (also known as the investment income) mainly includes the construction cost reduction caused by the decrease of repeated laying times of the pipeline, and the maintenance cost reduction caused by the decrease of pipeline breakage rate and leakage rate within the life cycle of UUT.…”
Section: The Benefit-based Proportional Allocation Methodsmentioning
confidence: 99%
“…Martin et al [37] analyzed the current scheme in order to address the carbon leakage implemented in the EU ETS. Liu and Fan [38] estimated the value-added based accounting of CO 2 Emissions (VBE), which was also named accumulated CO 2 emissions behind economic increase. They also found that emission importers would be helpful for emission exporters to reduce carbon emissions if the VBE system is applied [38].…”
Section: Literaturementioning
confidence: 99%
“…Liu and Fan [38] estimated the value-added based accounting of CO 2 Emissions (VBE), which was also named accumulated CO 2 emissions behind economic increase. They also found that emission importers would be helpful for emission exporters to reduce carbon emissions if the VBE system is applied [38]. Finally, Barker et al [39] studied the potential carbon leakage in six examples of ETRs in Europe by measuring the carbon leakage.…”
Section: Literaturementioning
confidence: 99%